PENGARUH FAKTOR ORGANISASIONAL PADA STRES KERJA PEGAWAI DENGAN GENDER SEBAGAI VARIABEL PEMODERASI (Studi pada Tenaga Kependidikan Universitas Tunas Pembangunan) - MRIHRAHAYU RUMANINGSIH (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2014)
The purpose of this study areÂ 1) Testing the influence of organizational variables (conflict, career barriers, excess workload, work environment unpleasant and alienation) on job stress. 2) Testing the influence of gender as a variable moderating variables on work stress. Research conducted at the University of Tunas Pebangunan Surakarta. The population in this study is the entire educational staff is available at the University of Tunas Pembangunan Surakarta by 70 people. The samples taken were 70 academic staff as respondents. Sampling technique using saturated sampling that all members of the population sampled. Methods of data collection using questionnaires with data analysis using hierarchical regression analysis, t test, and F test. The results of the hierarchical regression analysis found that the main effect of the stress of work contained in the University of Tunas Pebangunan Surakarta is the role of conflict, alienation, workload, work environment and career obstacles. Stress employees work at the University of Tunas Pebangunan Surakarta can be explained by organizational factors which consist of role conflict, alienation, workload, work environment and career barriers and gender by 98 % , while the remaining 12 % is explained by other factors beyond our model this. The interaction of role conflict and career barriers in the presence of gender as a variable moderating effect of work stress weakens. It is evident from the variable role conflict and career barriers significantly positively while the other variables are not significant, so the variable factors of organizational interaction with gender shows that the smaller the effect of the stress of work. From these results it can be stated that the gender of job stress can weaken the employees at the University of Tunas Pebangunan Surakarta.